Percepción de estrés en personal universitario (2015)
The aim of the study was to analyze the level of stress perceived by the administration and service staff (pas) of the University of Granada (ugr) in a scientific and technical campus. We obtained a sample of 194 women and 156 men. The perceived stress levels in subjects who participated in the study were evaluated by Perceived Stress Scale (pss). Statistical analyzes compared the level of perceived stress with different sociodemographic factors such as age, marital status, number of children, time worked at the university, type of contract, dependents persons performing physical activity or consumption of any kind of toxic substances, such as alcohol or snuff. Each of these factors was analyzed taking into account the gender perspective. The results show statistically significant differences in the level of perceived stress in some of the factors that we have analyzed.